Stereotactic Body Radiotherapy versus Low Dose Rate Brachytherapy for Localised Prostate Cancer: a Cost–Utility Analysis. Issue 11 (November 2017) - Helou, J.; Torres, S.; Musunuru, H.B.; Raphael, J.; Cheung, P.; Vesprini, D.; Chung, H.T.; D'Alimonte, L.; Krahn, M.; Morton, G.; Loblaw, A.
Abstract: Aims: To conduct a cost–utility analysis comparing stereotactic body radiotherapy (SBRT) with low dose rate brachytherapy (LDR-BT) for localised prostate cancer (PCa). Materials and methods: A decision-analytic Markov model was developed from the healthcare payer perspective to simulate the history of a 66-year-old man with low-risk PCa. The model followed patients yearly over their remaining lifetimes. Health states included 'recurrence-free', 'biochemical recurrence' (BR), 'metastatic' and 'death'. Transition probabilities were based on a retrospective cohort analysis undertaken at our institution. Utilities were derived from the literature. Costs were assigned in 2015 Canadian dollars ($) and reflected Ontario's health system and departmental costs. Outcomes included quality-adjusted life years (QALYs), costs and incremental cost-effectiveness ratios. A willingness-to-pay threshold of $50 000/QALY was used. Results: SBRT was the dominant strategy with 0.008LYs and 0.029QALYs gained and a reduction in cost of $2615. Under base case conditions, our results were sensitive to the BR probability associated with both strategies. LDR-BT becomes the preferred strategy if the BR with SBRT is 1.3*[baseline BR_SBRT] or if the BR with LDR-BT is 0.76*[baseline BR_LDR-BT]. When assuming the same BR for both strategies, LDR-BT becomes marginally more effective with 0.009QALYs gained at a cost of $272 848/QALY. Conclusions: SBRT represents an economically attractive radiation strategy. Further research should be carried out to provide longer-term follow-up and high-quality evidence. Highlights: A cost–utility analysis comparing stereotactic body radiotherapy (SBRT) with low dose rate brachytherapy in the treatment of localised prostate cancer was conducted. A decision-analytic Markov model was developed from the Ontario healthcare payer perspective. SBRT is an economically attractive radiation strategy.